Kako oblikovati organizacijski model športnih dejavnosti na UL za prihodnje generacije študentov - Filipič-Jeras, Ksenija (Šport (Ljubljana), 2019)
Attempts of refreshing and harmonizing the old programs of regular physical education and extracurricular sports activity with the introduction of the Bologna study programs have not achieved the desired results neither at the University of Ljubljana nor the wider Slovenian university area. University sports today are represent by required and optional regular programs of physical education and general elective ECTS courses in first and second phases of study programs of members, by extracurricular activities of the Centre of university sports which is also credited and competitive sport, guided by Sports Association of the University of Ljubljana. Share of students regularly active in sport has been declining more than it should for some years despite the fact that since 2005, the UL operates two systems. Established and defined legal system is needed so that we will have a common ground for all members of UL and for laying down minimum standards in the wider Slovenian university area.
Keywords: ECTS course; ECTS predmet; extra-curricular activity; obštudijske dejavnosti; organizacijski modeli; organizational models; regular sports education; students; športna vzgoja; študenti; študijski programi; University of Ljubljana; university sport; Univerza v Ljubljani; univerzitetni šport